Service innovation: A service blueprinting for Industry4.0 - Silva, Agostinho (2021)
This research aims to conceptualize a service blueprinting framework to map the digital interaction and shared access to service system resources in Industry 4.0 operations. From the literature review we found that in Industry 4.0 operations, customer and provider are value co-creators, and thus, mapping the service process using such service blueprinting becomes useful to boost new dynamics generating positive and measurable innovation outcomes using either quantitative or qualitative indicators, indexed to the different stakeholders’ concerns. As recommended by the of Service Science, wealth comes from service innovation among service systems, so, it is necessary to know at the outset which resources are involved in value propositions along the service process. With this research, we have conceptualized an innovative service blueprinting framework for the digital innovation to visualize the bridge between the physical world and the virtual world in Industry 4.0 operations.